Public views on the Central Highland National Park - conditions for a consensus among recreational users - Michael Bishop 1993- (2020)
The establishment of a National Park in the Central Highland of Iceland, now on the forefront of the political agenda, would set a milestone in the nature conservation history of Iceland and constitute the largest national park in Europe. While this project enjoys a broad public support, underlying expectations and reluctances have not been documented. Using a nation-wide quantitative survey, the general aim of this research is to provide a more comprehensive overview of the public attitudes towards the proposed national park and related land-use issues. The results confirm that the park is widely supported by the public and reveal that their views on road and accommodation development are however much more divided. These divergences point to potential conflict areas that should be addressed while establishing the National Park. Beyond conservation objectives, supporters of the park put a strong emphasis on its ability to manage tourism in the area, while the opposition is concerned by the reduction of opportunities for public outdoor recreation, the operational cost of the park and governance issues. The users of the area expressed more polarized views than non-users towards the park and road developments, and differences among them were observed in regard with their recreational profiles. From a management perspective, this study concludes that stakeholder consultation is of a vital importance to address their expectations and secure a broader consensus among the users of the area. Stofnun þjóðgarðs á miðhálendi Íslands myndi marka tímamót í sögu náttúruverndar hér á landi og jafnframt verða stærsti þjóðgarður Evrópu. Þrátt fyrir víðtækan stuðning almennings til fyrirhugaðs þjóðgarðs, er enn sem komið er lítið vitað um undirliggjandi væntingar almennings til þjóðgarðs, sem og andstöðu við hann. Meginmarkmið þessarar rannsóknar var að meta viðhorf almennings til þjóðgarðs á miðhálendinu, sem og til ágreiningsmála vegna nýtingar lands á svæðinu sem hann mun ná yfir. Niðurstöður sýna mikinn stuðning við ...